PROSPECTS FOR THE ISLAMIC BANKING DEVELOPMENT IN RUSSIA (Вестник университета)
The development of Islamic banking in Russia and in the world was analyzed. The patterns of the functioning of Islamic nance and banking were revealed. The prospects for involving Islamic nance in the state nancial system and the development of Islamic banking were shown. Specic proposals aimed at expanding Islamic banking in Russia were formulated: the developing legislative acts, using the Bank of Russia regulatory sandboxes, the Islamic banking to nance infrastructure projects, in conjunction with Russian development institutions.